\(In vitro\) regeneration of \(Renanthera imschootiana\) Rolfe from protocorm-like body - Nie Bing, H’Yon; Thai Vinh, Tran; Kim Cong, Vu; Thi Tham, Dang; Duy, Nong Van (Academia Journal of Biology, 2023)
Renanthera imschootiana Rolfe is an extremely rare and endangered tropical epiphytic orchid. Studies on in vitro culture of R. imschootiana were conducted in order to conserve and increase the genetic pool of this wild orchid species. In this study, the effect of plant growth regulators (BA and NAA), ripe bananas in combination with potato, humic acid, and silver nanoparticles (AgNPs) were investigated to find a suitable condition for in vitro plant regeneration from R. imschootiana protocorm-like body (PLB). The results showed that after 45 days of culture, MS medium supplemented with 100 g ripe banana/liter and 100 g potato/liter was suitable for regenerating shoots from the protocorm-like body (PLB) (17.56 shoots/PLBs and 100.00% of shoot-regenerating PLBs); MS medium supplemented with 2.0 mg/L BA, 0.3 mg/L NAA and 4 ppm AgNPs was the most suitable for the growth of shoots after 60 days of culture (10.00 leaves/shoot and shoot length of 4.22 cm). The in vitro shoots were transferred to half-strength MS supplemented with humic acid and AgNPs to investigate the root formation of R. imschootiana. After 60 days of culture, the best rooting was obtained at 2.0 mg/L humic acid and 6 ppm AgNPs (8.33 roots/shoot; root length of 4.00 cm and 100.00% root formation). The findings suggest that the in vitro micropropagation from R. imschootiana protocorm-like body provides a useful alternative tool for the conservation of this endangered species.